TEACHING INTERNSHIP IN MASTER’S DEGREE IN DENTAL SCIENCES: AN EXPERIENCE REPORTTEACHING INTERNSHIP IN MASTER’S DEGREE IN DENTAL SCIENCES: AN EXPERIENCE REPORT: ESTÁGIO DOCÊNCIA NA FORMAÇÃO DO MESTRE EM CIÊNCIAS ODONTOLÓGICAS: RELATO DE EXPERIÊNCIA - Dantas Torres de Araújo, Isabela; Castillo Dutra Borges , Boniek (Cadernos ESP, 2020)
Universities are important opinion-makers and knowledge generators anchored in the pillars of teaching, research, and extension. Thus, it was established that the master and doctorate students should be included in these activities under supervision. The present study is a report about the activities developed and the experience lived in the Teaching Internship in the Dentistry course of the Federal University of Rio Grande do Norte. The internship lasted one year starting in the second semester of 2018 as a voluntary internship and concluding in the first semester of 2019 as a compulsory internship. An assisted teaching plan and a semiannual report were developed as a prerequisite for the internship. The teaching internship provided an opportunity for interrelationship that went beyond content and plans, exceeding the expectation of dealing with complex situations.
Keywords: Teaching; Dentistry; Interpersonal relations